Construction of Versatile and Functional Nanostructures Derived from CO2‐based Polycarbonates1. Issue 35 (15th July 2015) - Wang, Yanyan; Fan, Jingwei; Darensbourg, Donald J.
Abstract The construction of amphiphilic polycarbonates through epoxides/CO2 coupling is a challenging aim to provide more diverse CO2‐based functional materials. In this report, we demonstrate the facile preparation of diverse and functional nanoparticles derived from a CO2‐based triblock polycarbonate system. By the judicious use of water as chain‐transfer reagent in the propylene oxide/CO2 polymerization, poly(propylene carbonate (PPC) diols are successfully produced and serve as macroinitiators in the subsequent allyl glycidyl ether/CO2 coupling reaction. The resulting ABA triblock polycarbonate can be further functionalized with various thiols by radical mediated thiol–ene click chemistry, followed by self‐assembly in deionized water to construct a versatile and functional nanostructure system. This class of amphiphilic polycarbonates could embody a powerful platform for biomedical applications.